Correlation of Ceramic Dust Content in Workplace with Lung Function in Ceramics Industry Workers of X Company, Mabar, Medan - Endy Todo Sirait; Amira Permatasari Tarigan; Nuryunita Nainggolan; Putri Chairani Eyanoer (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Workers in the ceramics industry are often exposed to silica content which is unwittingly inhaled and deposited in the lungs. Macrophages will release Interleukin 8 (IL-8), a chemoattractant that causes neutrophil recruitment to the alveoli and releases proteolytic enzymes that damage the lung parenchyma and cause a decrease in lung function. This study aimed to determine whether dust level correlate with IL-8 serum in ceramic industry workers. Method: This research is an analytic study with a cross-sectional design conducted in March–June 2019 in the X Ceramic Industry in Mabar, Medan. Personal Dust Sampler was used to measure dust level of the study subjects at work sites. Lung function was measured by spirometry. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) software. Results: A total of 35 male workers were divided into 3 working sections, 11 (31.4%) in the pre-compression section, 13 (37.1%) in the compression section and 11 (31.4%) in the sintering section. Dust levels at each working section were 24.8, 29.2, and 6.11, respectively. The lung function examination showed restrictive impairment in 21 subjects (60%). Statistical analysis showed that the higher the level of dust in the workplace, the lower the value of Forced Expiratory Volume 1 (FEV1) and Forced Vital Capacity (FVC) values, although this correlation was not statistically significant (r = -0.03 and -0.22 respectively; p> 0.05). Conclusion: There was no significant relationship between workplace dust levels and lung function in ceramic workers.